Female Broodstock Reproductive Output, Larval Rearing And Spat Survival Of Black Lipped Oyster (Pinctada Margaritifera) - Ehteshami, Fariborz (2010)

(untitled)
Overexploitation of Pinctada margaritifera as one of the natural resource was leading to a dramatic loss of its population in the north coast of Persian Gulf. Low abundance and density existing in the natural beds and poor larval recruitment prompted research on hatchery propagation of this species. Further research should be carried out to improve the survival and growth of larvae produced through artificial propagation. This study addressed important issues in relation to the supplementation of polyunsaturated fatty acids (PUFA) in diet and their role in egg quality and biochemical composition, and larval growth and survival; microalgae biochemical composition and its role in larvae culture; and spat settlement and transfer time to the sea farm. In the first experiment, the effects of supplementary PUFA on oogenesis and hatching rate of P. margaritifera broodstock were compared with naturally fed oysters and those fed only microalgae. Supplementary food was effective (P < 0.05) on producing larger sized eggs (57.6 μm) and larvae (80.1 μm), and higher percentage of P. margaritifera D shape larvae (31.3%). Palmitic (16:0) and stearic (18:0) acid were the major saturated fatty acids in neutral and polar parts of gonad lipid. Oysters fed with supplementary PUFA had more docosahexaenoic acid (DHA) and less monounsaturated fatty acids (MUFA) in their gonad. The ratio of n-3/n-6 fatty acids in neutral lipid was the best representative of differences in conditioning of oysters for spawning and interpretation of the results of egg size and hatching performance. In the second experiment, the effects of partial supplementation of the diet with PUFA on growth and survival of P. margaritifera D-shape and umbo larvae were investigated. PUFA supplemented in droplet form did not increase the growth and survival of D-shape and umbo P. margaritifera larvae compared to those fed fresh algae of T. Iso (P > 0.05). Considering results of size range of larvae, it can be concluded that through the grading process, a great number of larvae would be lost in treatments with supplementary diet compared to those fed with T. Iso only. D-shape and umbo larvae showed a similar performance in survival, with the highest related to larvae fed with fresh algae followed by 10, 30 and 100% of diet replaced with PUFA emulsions. While the lowest survival attributed to the unfed larvae.